"Я надеюсь... ": [беседы с Г. Пряхиным о себе, прожитом и настоящем] / Р. М. Горбачева - Горбачева Раиса Максимовна (Книга, 1991)
Экземпляры: ф.18 (1992) / Инвентарный номер: 35880 / Цена: / Сис.шифр: 66.3(2)8 / Авт.знак: Г 67 / ГРНТИ: 11.15 / ББК: 66.3(2)8